Antibacterial and Anti-Inflammatory Activity of an Antimicrobial Peptide Synthesized with D Amino Acids - Jlenia Brunetti; Veronica Carnicelli; Alessia Ponzi; Antonio Di Giulio; Anna Rita Lizzi; Loredana Cristiano; Laura Cresti; Giovanni Cappello; Simona Pollini; Lara Mosconi; Gian Maria Rossolini; Luisa Bracci; et al. (MDPI AG, 2020)
The peptide SET-M33 is a molecule synthesized in tetra-branched form which is being developed as a new antibiotic against Gram-negative bacteria. Its isomeric form with D amino acids instead of the L version (SET-M33D) is also able to kill Gram-positive bacteria because of its higher resistance to bacterial proteases (Falciani et al., PLoS ONE, 2012, 7, e46259). Here we report the strong in vitro activity of SET-M33D (MIC range 0.7-6.0 µM) against multiresistant pathogens of clinical interest, including Gram-positives Staphylococcus aureus, Staphylococcus saprophyticus, and Enterococcus faecalis, and various Gram-negative enterobacteriaceae. SET-M33D antibacterial activity is also confirmed in vivo against a MRSA strain of S. aureus with doses perfectly compatible with clinical use (5 and 2.5 mg/Kg). Moreover, SET-M33D strongly neutralized lipopolysaccharide (LPS) and lipoteichoic acid (LTA), thus exerting a strong anti-inflammatory effect, reducing expression of cytokines, enzymes, and transcription factors (TNF-α, IL6, COX-2, KC, MIP-1, IP10, iNOS, NF-κB) involved in the onset and evolution of the inflammatory process. These results, along with in vitro and in vivo toxicity data and the low frequency of resistance selection reported here, make SET-M33D a strong candidate for the development of a new broad spectrum antibiotic.